Copyright and Accessibility in South African Research Archives - Walker, Andrea (Department of Commercial Law, 2024)
Research archives aim to achieve a balance between preservation and access. Copyright law aims to achieve a balance between the interests of rightsholders and users. These aims sound broadly similar at first, but there are areas where the intersection can be problematic. This dissertation examines the problem of archival accessibility through three lenses: copyright duration, preservation, and third-party and orphan works. Copyright assumes an author intends to exploit their work through some form of publication. Most of the works within a research archives are unpublished. One of the ways archives seek to make works more accessible to more people, is by placing them online. Unless the copyright has expired or been assigned to the archives, this requires permission from the rightsholder(s). In South Africa, many unpublished works have perpetual copyright. Determining when the copyright expires—if it expires—is complicated by more than publication status. Certain works require reference to otherwise repealed laws due to the transitional provisions that continue to apply to archival works long after the transition has taken place. The question of internet ‘publishing' also needs to be considered. In order to make works accessible in perpetuity, the works need to be preserved so that they continue to exist. To preserve works, archives need to reproduce them. The Copyright Regulations allow the creation of facsimile copies for preservation purposes without requiring the permission of the rightsholder(s). If the reproduction is not in facsimile form, then it is infringement without the rightsholder(s) permission. It is not clear if the format shifting that audiovisual and digital content requires is allowed when creating a facsimile. This material becomes inaccessible and is lost very quickly as format shifting is needed in order to keep the content accessible, as well as to preserve it for the long-term. Copyright and Accessibility in South African Research Archives | Andrea Walker | ii Many archival works, such as letters, are authored by third-parties—that is, someone other than the person or corporate body who created the bulk of the collection. Many of these become orphan works as identifying and locating the rightsholder(s) with limited information is very difficult. Works with perpetual copyright frequently become orphaned as tracing the author's descendants and their subsequent heirs and any licences or assignments is a lengthy and difficult process. The inability to identify and locate rightsholders does not only impact on accessibility, but also preservation. There are some simple solutions to these problems, but while suggestions for improvements are offered, most of these are not issues that can easily be dealt with.